2022
DOI: 10.1371/journal.pone.0273149
|View full text |Cite
|
Sign up to set email alerts
|

Using a learning health system framework to examine COVID-19 pandemic planning and response at a Canadian Health Centre

Abstract: Background The COVID-19 pandemic has presented a unique opportunity to explore how health systems adapt under rapid and constant change and develop a better understanding of health system transformation. Learning health systems (LHS) have been proposed as an ideal structure to inform a data-driven response to a public health emergency like COVID-19. The aim of this study was to use a LHS framework to identify assets and gaps in health system pandemic planning and response during the initial stages of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Based on our findings, building relationships among and across different sectors in and out of the health system was a big concern for Iran's national policymakers in the first months of the epidemic. We considered such policy interventions as policies that support the learning capacities, and data linkage of the health system 7,9 . However, the study findings showed that there was no policy that could be considered a significant improvement for the culture and competencies of RLHS, as they were defined 9 during the study time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our findings, building relationships among and across different sectors in and out of the health system was a big concern for Iran's national policymakers in the first months of the epidemic. We considered such policy interventions as policies that support the learning capacities, and data linkage of the health system 7,9 . However, the study findings showed that there was no policy that could be considered a significant improvement for the culture and competencies of RLHS, as they were defined 9 during the study time.…”
Section: Discussionmentioning
confidence: 99%
“…We considered such policy interventions as policies that support the learning capacities, and data linkage of the health system. 7,9 However, the study findings showed that there was no policy that could be considered a significant improvement for the culture and competencies of RLHS, as they were defined 9 during the study time.…”
Section: The Content Of Policy Interventions Introduced To Control Co...mentioning
confidence: 94%
See 2 more Smart Citations
“…Although advancements have been made, the health care data asset-to-utilization ratio remains low [ 3 ]. There is a growing recognition of the critical need to establish learning health care systems (LHSs) within and across health care organizations, a need that has been exponentially exacerbated during the COVID-19 pandemic [ 4 , 5 ]. Conceptually, LHSs enable hospitals to function as active learning environments, where evidence synthesis from real-world data is a by-product of clinical care [ 6 ].…”
Section: Introductionmentioning
confidence: 99%